Functional disability in community-dwelling elderly: the role of cataracts and contextual factors - Larissa de Lima Borges; Fernanda Pains Vieira dos Santos; Valéria Pagotto; Ruth Losada de Menezes
Introduction Cataract arises as a risk factor for functional disability in elderly Objective: To determine differences in functional capacity and contextual factors associated with it in elderly affected and not affected by cataract and association between disability and cataracts.Methods A transversal-type observational study was carried out with 100 community elderly, divided into two groups: elderly affected (n = 50) and not affected by cataracts (n = 50). It was evaluated: activities of daily living (ADL) - Katz Index -, instrumental activities of daily living (IADL) - Lawton scale - and mobility - Short Physical Performance Battery. Functional disability was detected when the elderly were dependent or semi-dependent for one or more IADL or ADL and/or when they presented any difficulty in mobility. Data analysis included absolute and relative frequencies, Chi-squared or Fisher's exact tests (p < 0.05) and Poisson regression.Results No statistically significant associations were observed between IADL, ADL or mobility disability and cataracts. A statistically significant difference was observed between the disabled elderly affected and not affected by cataract according to contextual factors for ADL regarding age (p = 0.037) and comorbidity (p = 0.037), for mobility regarding the practice of physical activity (p = 0.013), and for IADL (p = 0.001), ADL (p = 0.001) and mobility (p = 0.013) regarding the self-reporting of eyesight problems.Conclusions Besides cataracts, physical inactivity, comorbidity and functional aging itself are contributing factors to the process of disability in elderly, so, the physiotherapy is essential both to prevent as to reverse this process.